Ursus arctos Linnaeus 1758 - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Ursus arctos Linnaeus, 1758 —Brown Bear Ursus arctos Linnaeus, 1758 p.47; Type locality- Sweden; Won, 1968 p.271; Han, 1994 p.46; Won & Smith, 1999 p.17; Oh, 2004a p.165. U. lasiotus Gray, 1867 p.301; Type locality- interior of northern China. Melanarctos cavifrons Heude, 1901 p.1; Type locality- northwestern Manchuria. U. cavifrons : Kishida & Mori, 1931 p.379. U. arctos lasiotus : Kuroda, 1938 p.31; Ellerman & Morrison-Scott, 1951 p.238; Won, 1958 p.440; Won, 1967 p.122; Won, 1968 p.273. U. arctos arctos : Yoon, 1992 p.99. Range: The distribution of U. arctos covers most northern alpine habitats and extends to the southern boundary at Mt. Geumgang (Kim et al. 2015; Fig. 40). Although this bear species was recorded around Mt. Baekdu until the 1980s, the current presence in the Mt. Geumgang and Mt. Baekdu areas in North Korea remains uncertain. Remarks: The Subspecies U. a. lasiotus Gray, 1867, Ussuri brown bear (or Amur brown bear, black grizzly or horse bear) in northeastern Asia traditionally included the Korean Peninsula. Conservation status: North Korea designated two brown bear habitats (Ryongrim, Jagang Province and Gwanmobong, Hamgyeongbuk Province) as Natural Monuments in 1980. The Red Data Book of North Korea lists this species as ‘Vulnerable’ (MAB National Committee of DPR Korea 2002). Populations in China and Mongolia are protected by CITES Appendix I and Russian populations are protected by Appendix II. Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 65, DOI:10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198